Study on the Modeling Method and Influencing Parameters of Sandblasting Process for Blade Grinding. (9th March 2022) - Yu, Xiangyong; Wei, Xiuting; Huang, Xuemei; Zhang, Leian
Abstract : Grinding the surface of wind turbine blades is one of the key production processes before its service. In order to solve the problem of high labor cost and low precision in manual grinding wheel grinding of wind turbine blades, the sandblasting process for blade grinding is proposed. The best parameters of sandblasting process applied to wind turbine blades are investigated by simulation. In this study, the simulation model of sandblasting process is established, and the fluid analysis of blades' grinding using sandblasting process is carried out with the variables of blasting pressure, abrasive diameter, and blast distance. Simulation results show that the best parameters are 0.7 MPa for blasting pressure, 500 mm for spraying distance, and 0.4 mm for abrasive diameter. Finally, the tensile test is carried out on the samples' grind by the traditional grinding process and sandblasting process. The results show that the paint surface grind by sandblasting process can bear a higher load. This study proves the feasibility of the sandblasting process in the composite materials' grinding of wind turbine blades.